2017
DOI: 10.1634/theoncologist.2016-0283
|View full text |Cite
|
Sign up to set email alerts
|

Escalating Health Care Expenditures in Cancer Decedents’ Last Year of Life: A Decade of Evidence from a Retrospective Population-Based Cohort Study in Taiwan

Abstract: Background. No population-based longitudinal studies on endof-life (EOL) expenditures were found for cancer decedents.Methods. This population-based, retrospective cohort study examined health care expenditures from 2001 to 2010 among 339,546 Taiwanese cancer decedents' last year of life. Individual patient-level data were linked from administrative datasets. Health care expenditures were converted from Taiwan dollars to U.S. dollars by health-specific purchasing power parity conversions to account for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…1,2 One strategy to achieve this aim is advance care planning (ACP) 3 to explore patient preferences for life-sustaining treatments (LSTs) 4,5 and clarify misunderstandings 6 about their efficacy at EoL, actively involve patients in EoL care decision-making, and align EoL care with patients' goals and preferences. 1,2,4,5 Providing such value-based EoL care to terminally ill patients with cancer may not only "individualize" EoL cancer care 2 and counteract the international trend toward increasingly aggressive and costly EoL care, [7][8][9] but also may facilitate adjustment to the uncertainty inherent in EoL care decision-making, thus alleviating anxiety and depressive symptoms and improving quality of life (QoL). 10,11 The few randomized controlled trials (RCTs) of ACP studies targeting terminally/seriously ill patients [12][13][14][15][16][17][18][19] have shown that ACP not only increases physicianpatient EoL care discussions, [12][13][14][15][16][17][18][19] (earlier) completion of advance directives, 13,[16][17][18] and concordance between preferred and received EoL care, 13,16 but also does not detrimentally affect patients' anxiety, depression, and QoL.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 One strategy to achieve this aim is advance care planning (ACP) 3 to explore patient preferences for life-sustaining treatments (LSTs) 4,5 and clarify misunderstandings 6 about their efficacy at EoL, actively involve patients in EoL care decision-making, and align EoL care with patients' goals and preferences. 1,2,4,5 Providing such value-based EoL care to terminally ill patients with cancer may not only "individualize" EoL cancer care 2 and counteract the international trend toward increasingly aggressive and costly EoL care, [7][8][9] but also may facilitate adjustment to the uncertainty inherent in EoL care decision-making, thus alleviating anxiety and depressive symptoms and improving quality of life (QoL). 10,11 The few randomized controlled trials (RCTs) of ACP studies targeting terminally/seriously ill patients [12][13][14][15][16][17][18][19] have shown that ACP not only increases physicianpatient EoL care discussions, [12][13][14][15][16][17][18][19] (earlier) completion of advance directives, 13,[16][17][18] and concordance between preferred and received EoL care, 13,16 but also does not detrimentally affect patients' anxiety, depression, and QoL.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study in seven developed countries showed that 40.3% of patients were admitted to the ICU in the USA and approximately 18% of patients were admitted to the ICU in the six other countries 42. The mean cost is US$18 234 per capita, which is lower than those of developed countries, such as Canada (US$21 840), Norway (US$19 783), the USA (US$18 500),42 South Korea, Japan and Taiwan (annual cost of US$68 773 in 2010) 43. The cost increased dramatically as death approached, similar to the results that SEER-Medicare costs revealed 44.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be related to the traditional Chinese concept of death and suggests ineffective and irrational utilisation and low-value service provision 50. However, this finding is inconsistent with the conclusion that patients prefer to receive relatively passive care in Taiwan 43. Third, cost also depends on the place of death, and cost increased rapidly as death approached.…”
Section: Discussionmentioning
confidence: 99%
“…14 Therefore, hospice care should be offered not only shortly before death (i.e., within the last month of life) but also throughout the dying trajectory (i.e., in the last six months of life) to improve quality of life at EOL. In this way, hospice care may more effectively mitigate the trend of increasingly aggressive cancer care and escalating cancer care expenditures, 8,9,11 thereby ensuring the sustainability of health care systems for cancer patients and facilitating a better dying experience for terminally ill cancer patients.…”
Section: Discussionmentioning
confidence: 99%